Risk management: Factors Influencing the Failure of Residential Infrastructure Development in Bekasi, West Java - Suryadi, Dedy; Herwindiati, Dyah Erny; Anondho, Basuki; Sari, Endah Murtiana (International Journal of Innovative Research and Scientific Studies, 2025)
Infrastructure development in a residential area has a high economic and social impact, so the success of infrastructure development is very important for the community, which will have a wider impact on life. Bekasi Regency is the area with the largest population in the Jakarta area, so infrastructure development is carried out massively to meet the needs of the population in order to develop its area economically and socially. The problem of infrastructure development currently often fails, where the function of infrastructure cannot be utilized optimally by the community. This study aims to evaluate the factors that influence the failure of residential infrastructure development in Bekasi, West Java. The failure of infrastructure development is an obstacle to development and improving the quality of life of the community in Bekasi, West Java. Through a quantitative method with 200 respondents, the results were then analyzed using SEM (structural equation model). This study maps that there are 3 (three) dimensions of risk that must be considered in influencing the failure of infrastructure development in Bekasi, with a total of 32 factors considered to influence it. The results of this study indicate that a number of external risk factors have a significant impact on the failure of infrastructure development in Bekasi, while internal risk factors and project risks are considered to be risks that can be controlled by the contractor. If managed properly, they do not have a significant impact. This study will provide an evaluation of project risk management in residential infrastructure development in Bekasi, which can be utilized by contractors, local governments, academics, the community, and anyone who wants to conduct evaluations and implement strategies to avoid failure in infrastructure development in the future.